On-the-Job Search and the Beveridge Curve - Fuentes, Andres (IMF Working Papers; Working Paper, 2002)
This paper presents a theoretical and empirical investigation of the role on-the-job search plays in explaining shifts of the unemployment-vacancies relationship (the Beveridge curve). We show that the direction of the shift depends on the parameters of the matching model, regardless of the assumptions made on the relative search effectiveness of employed and unemployed searchers. We estimate a Beveridge Curve equation with a panel of British regions controlling for unobserved aggregate unemployment effects. We find evidence that the rise in on-the-job search in the 1980s has shifted the Beveridge Curve outwards.